Female homosexuality in ancient Greece and Rome - Boehringer, Sandra 1972- (Routledge, 2021)
"This groundbreaking study, among the earliest syntheses on female homosexuality throughout antiquity, explores the topic with careful reference to ancient concepts and views, drawing fully on the existing visual and written record including literary, philosophical, and scientific documents. Even today, ancient female homosexuals are still too often seen in terms of a mythical, ethereal Sapphic love, or stereotyped as "Amazons" or courtesans. Boehringer's scholarly book replaces these clichés with rigorous, precise analysis of iconography and texts by Sappho, Plato, Ovid, Juvenal, and many other lyric poets, satirists, and medical writers, in search of the prevailing norms, constraints, and possibilities for erotic desire. The portrait emerges of an ancient society to which today's sexual categories do not apply - a society "before sexuality" - where female homosexuality looks very different, but is nonetheless very real. Now available in English for the first time, Female Homosexuality in Ancient Greece and Rome includes a preface by David Halperin. The book will be of value to students and scholars of ancient sexuality and gender, and to anyone interested in histories and theories of sexuality"--
Keywords: Geschichte; Lesbische Orientierung -- Motiv; Römisches Reich; Griechenland -- Altertum; Lesbianism / Greece / History; Lesbianism / Rome / History; Lesbianism / Mythology / History